Intracortical synchronization pattern on the preclinical and clinical stages of absence epilepsy (analysis of wavelet bicoherence in WAG/Rij rats) - Sitnikova, Evgenia; Rutskova, Elizaveta; Smirnov, Kirill; Runnova, Anastasiya; Zhuravlev, Maksim (The European physical journal. ST, Special topics, 2023)
Here we examine the intracortical synchronization pattern in freely moving WAG/Rij rats (valid animal model of absence epilepsy). In all rats, electrocorticograms were recorded at the age 5 and 9 months (i.e., preclinical and clinical stages of absence epilepsy in epileptic subjects). To assess intracortical synchronization pattern, we measured wavelet bicoherence in unilateral (fronto-frontal) and bilateral (fronto-occipital) electrode pairs in five non-overlapping frequency bands (“1–4 Hz”; “5–9 Hz”; “9–12 Hz”; “12–14 Hz”; “14–20 Hz”) and two additional bands “0.5–1.5 Hz”; “10–14 Hz” bands. Bilateral fronto-frontal synchronization in epileptic subjects was lower than in non-epileptic ones only on the clinical stage of absence epilepsy. Unilateral fronto-occipital synchronization in epileptic rats was lower (“5–9 Hz” and “10–14 Hz”) than in non-epileptic ones only on preclinical stage. This finding may be interpreted as a marker of thalamo-cortical impairment associated with epileptogenic processes underlying long-term progression of absence epilepsy. We construct plots of synchronization patterns or diagnostic maps, which can be used for early diagnosis of absence epilepsy in predisposed subjects.